2010
DOI: 10.1007/s12274-010-1001-9
|View full text |Cite
|
Sign up to set email alerts
|

Shape control of CoO and LiCoO2 nanocrystals

Abstract: Shape control of nanocrystals has become a significant subject in materials science. In this work, we describe a convenient way to achieve morphology-controllable synthesis of CoO nanocrystals including octahedrons and spheres as well as LiCoO 2 polyhedrons and spheres. In particular, we explain the formation of CoO octahedrons exposing only high-energy (111) facets using theoretical calculations; these should also be a useful tool for directing future face-controlled preparation of other nanocrystals. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…For example, Wan's group has calculated that a reduction of diffusion length from 10 μm (the typical particle size of commercial electrode materials) to 100 nm, results in a decrease in the mean diffusion time from 5000 to 0.5 s [14]. Many reports have also demonstrated that smaller particles of electrode materials have shorter diffusion lengths for Li + , higher electrode/electrolyte contact areas, and better accommodation of the strain than common micron-sized materials [15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wan's group has calculated that a reduction of diffusion length from 10 μm (the typical particle size of commercial electrode materials) to 100 nm, results in a decrease in the mean diffusion time from 5000 to 0.5 s [14]. Many reports have also demonstrated that smaller particles of electrode materials have shorter diffusion lengths for Li + , higher electrode/electrolyte contact areas, and better accommodation of the strain than common micron-sized materials [15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…A calculation on different surfaces of cubic CoO indicates that the surface energy of (111) facets is higher than other low-index facets (e.g. (100) and (110) facets) [19]. Therefore the absorbed oleylamine molecules may protect {111} facets and eventually lead to the formation of octahedron nanocrystals with eight exposed {111} facets.…”
Section: Synthesis and Characterization Of Coo Nanocrystalsmentioning
confidence: 99%
“…For example, Nam synthesized CoO nano cubes and studied the electrochemical behaviors [16]. Wang et al reported the synthesis of octahedral CoO nanocrystals with sizes of 200 nm or even larger and characterized the electrochemical performance [19]. Zhang et al prepared CoO nanocrystals with various morphologies by turning surfactant concentration [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus various nanostructures of LiCoO 2 , including nanoparticles [9,10], nanoplates [11] and nanospheres [12] have been reported. However, onedimensional nanomaterials like nanowires, nanorods, nanotubes and nanobelts have only rarely been reported.…”
Section: Introductionmentioning
confidence: 99%